Implementation of Genetic Algorithm in Completion Traveling Salesman Problem Study Case of Garuda Express Delivery (GED) - Syariful Alim; M Mahaputra Putra; Bagus Damas Ardilestian; Agus Bintoro (Fakultas Teknik Universitas Bhayangkara, 2020)
Indaily distribution activities, GED is a shipping service company. Always associated with couriers as inter mediaries. Where each courier will send a packagetoseveraldifferent places.Surely they(couriers)want to immediately complete their tasks,by findingor determining the path that is traversed in order to shorten the work and return to the office and then make a report. This case is commonly called the Traveling Salesman Problem,which can be solved by several methods. One of them is by optimization of Genetic Algorithms. Genetic Algorithm methods can provide solutions to these problems by providing input (input) fromseveral addresses that they will (courier) distribute. Then the input will be processed with several stages starting from initialization, selection, crossover, mutation and regeneration. The results are then displayed in graphical form which links the shipping addresses. The results of the study, obtained the fastest route with a maximumof 10 points or shipping address,which can be used by the courier in its distribution. In this study, the objective valueisthe value of the length of the road section taken from the Google Map. With termination rules or conditions that state that the smallest and largest fitness values must be the same or 60% of the fitness of the genetic algorithm population shows the greatest fitness. This rule will give the same and accurate results even though the number of generations produced is different.